Problems and prospects for the use of nanofluids in thermal power engineering - A. N. Makeev; Ya. A. Kiryukhin (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the work is to study the use of nanofluids as heat carriers to increase the efficiency of heat removal in energy facilities. To solve this problem, materials of domestic and foreign scientific articles, conferences and dissertations on the subject of nanofluids were analyzed. Numerous scientific publications, including those cited in the international databases Web of Science and Scopus, indicate that the topic of nanofluids is in the focus of modern science. However, despite a rather long period of fluid research, not all issues of this topic are sufficiently well covered and systematized, which opens up great opportunities for further research in this direction.Method. When achieving this goal, the areas of possible application of fluids, the mechanism of their synthesis, the features of their operation are considered, the advantages as a liquid coolant are indicated, and the disadvantages that prevent their widespread use are identified. Particular attention is paid to such issues as: synthesis of standardized nanofluids; ensuring their stable properties; the use of surfactants; increasing the pressure drop inside heat exchangers during operation of this coolant.Result. To eliminate the main drawback in the form of agglomeration of nanoparticles in the base fluid, it is proposed to use the oscillatory circulation of the coolant, which will also further intensify heat exchange from forced turbulence of the fluid.Conclusion. The results obtained can be used to improve the efficiency of heat and mass transfer devices with liquid coolant and systems based on them, as well as to reduce the weight and size parameters of such devices.